2014
DOI: 10.1016/j.eururo.2014.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 Trial of Neoadjuvant Axitinib in Patients with Locally Advanced Nonmetastatic Clear Cell Renal Cell Carcinoma

Abstract: Background Previous studies have shown modest impact of tyrosine kinase inhibitors on primary renal tumors. These studies were mostly retrospective and heterogeneous in their eligibility criteria with regards to histology, disease stage, duration of therapy, and time off therapy prior to surgery. Objective To prospectively investigate the safety and efficacy of axitinib in downsizing tumors in patients with non-metastatic biopsy-proven clear cell renal cell carcinoma (ccRCC). Design, Setting, and Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 18 publications
6
113
1
4
Order By: Relevance
“…In the study by Karam and colleagues, five (21.8%) of 24 patients underwent partial nephrectomy after neoadjuvant axitinib therapy without any intraoperative or postoperative complications [Karam et al 2014]. It is important to note that undergoing a partial nephrectomy was also not a prespecified endpoint in the study.…”
Section: Changing the Unresectable To Resectablementioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Karam and colleagues, five (21.8%) of 24 patients underwent partial nephrectomy after neoadjuvant axitinib therapy without any intraoperative or postoperative complications [Karam et al 2014]. It is important to note that undergoing a partial nephrectomy was also not a prespecified endpoint in the study.…”
Section: Changing the Unresectable To Resectablementioning
confidence: 99%
“…Lastly, a recent phase II clinical trial published by Karam and colleagues reported on the experience with neoadjuvant axitinib in 24 patients with biopsy-proven clear cell locally advanced nonmetastatic RCC [Karam et al 2014]. Patients received daily axitinib for 12 weeks, which was discontinued only 36 h prior to nephrectomy.…”
Section: Tumor Downsizingmentioning
confidence: 99%
See 1 more Smart Citation
“…Given limited accrual to the randomized, phase II clinical trial reported herein, we are limited in our conclusions and can only suggest that axitinib is safe and well-tolerated in the neoadjuvant setting, consistent with findings from a neoadjuvant trial of axitinib in localized renal cell carcinoma (16). An ongoing study at the MD Anderson Cancer Center is comparing axitinib with ADT to axitinib alone before radical prostatectomy in a similar patient population (17).…”
Section: Discussionmentioning
confidence: 82%
“…A presurgical setting is ideal to make comparisons between radiologic and pathologic responses. Although the role of presurgical molecular-targeting therapy for advanced RCCs has not been clearly established, several studies have suggested a survival benefit [4][5][6][7][8][9][10][11] that corresponds to accumulating evidences of efficacy and safety. Here, we investigated the clinical implication of CMER in patients with advanced RCC who underwent presurgical molecular-targeting therapy followed by radical nephrectomy, and compared radiologic tumor responses by RECIST, Choi, and CMER with pathological outcomes in those patients.…”
Section: Introductionmentioning
confidence: 99%